2016
DOI: 10.1186/s13104-016-1923-8
|View full text |Cite
|
Sign up to set email alerts
|

Accidental exposures to blood and body fluids among health care workers in a Referral Hospital of Cameroon

Abstract: BackgroundAccidental exposure to blood and body fluids is a public health concern, especially among health workers and constitutes a risk of transmission of blood-borne viruses including HIV, hepatitis B virus and hepatitis C virus. The objective of this study was to determine the frequency and the post exposure management of accidental exposures to blood and body fluid among health workers in the Yaoundé University Teaching Hospital.MethodsIt was a cross-sectional hospital-based study conducted from the 1st t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
50
2
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(81 citation statements)
references
References 17 publications
8
50
2
12
Order By: Relevance
“…Our results are consistent with those of Kaya et al [1] , who reported that 93% of reported injuries were percutaneous, and 50.6% of these occurred during the needle recapping. In another study, the majority of exposures were mucosal contact due to splashes (60.3%), followed by needle-stick injuries (28.7%) [15] . In addition, according to our survey data, needles were the leading medical instrument causing injuries (77.55%, n=38), which corroborates the results of other similar studies.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Our results are consistent with those of Kaya et al [1] , who reported that 93% of reported injuries were percutaneous, and 50.6% of these occurred during the needle recapping. In another study, the majority of exposures were mucosal contact due to splashes (60.3%), followed by needle-stick injuries (28.7%) [15] . In addition, according to our survey data, needles were the leading medical instrument causing injuries (77.55%, n=38), which corroborates the results of other similar studies.…”
Section: Discussionmentioning
confidence: 92%
“…As in numerous studies from other countries [15,18] , Bozkurt et al [7] determined that nurses were the occupational group at greatest risk of injury in Turkey. However, in our study the cleaning staff received the most injuries, similar to the findings of Merih et al [13] , followed by nurses and midwives.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accidental exposure to BBFs is the unintended contact with blood and or body fluids mixed with blood, during a medical intervention [5]. HCWs are at increased risk of this exposure and acquiring infections including hepatitis virus and HIV because of direct chance of exposure they have to patients blood and other body fluids [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%